The influence of managerial competency and job satisfaction on the performance of teachers of negatiary schools - Sri Wati; Happy Fitria; Syaiful Eddy (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
This study aims to determine the effect of managerial competence and job satisfaction together on teacher performance. The location of this research was carried out in SD Negeri all Babat Supat District, Musi Banyuasin Regency. This type of research is a quantitative study with a determination design using an ex post facto research design. The sample in this study was the total of all teachers in SD Negeri in Babat Supat District, Musi Banyuasin Regency, consisting of 174 teachers. data collection techniques using a questionnaire. The data analysis technique used quantitative descriptive analysis techniques and multiple regression. The results of this study indicate that 1) there is a significant influence between managerial competence on the performance of public elementary school teachers in Babat Supat District, Musi Banyuasin Regency; 2) there is a significant influence between job satisfaction on the performance of SD Negeri teachers in Babat Supat District, Musi Banyuasin Regency; 3) there is a significant effect jointly between managerial competence and job satisfaction on the performance of SD Negeri teachers in Babat Supat District, Musi Banyuasin Regency.